Pengaruh Pelatihan dan Kompetensi Kerja terhadap Kinerja Karyawan Pada PT Cahaya Persada Multiarta Tangerang Selatan - Qurbani, Usama Derita (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to determine the extent of the positive influence of training and work competence on employee performance at PT Cahaya Persada Multiarta Tangerang Selatan, both partially and simultaneously. This study uses a quantitative research method with an associative analysis approach. The sample used in this study is a saturated sample, meaning the entire population of 55 individuals was included. There is an influence of training and work competence on employee performance with the regression equation Y = 14.502 + 0.382X1 + 0.256 X2, with a correlation coefficient of 0.657, meaning that Training and Work Competence have a strong relationship. The coefficient of determination or the simultaneous contribution of influence is 65.7%. The hypothesis test yields an F-calculated value ≥ F-table value or (19.795 ≥ 3.180). Therefore, H03 is rejected and Ha3 is accepted, meaning it can be concluded that the variables of training and job competence significantly influence employee performance.